2009
DOI: 10.3748/wjg.15.226
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to surveillance guidelines for dysplasia and colorectal carcinoma in ulcerative and Crohn’s colitis patients in the Netherlands

Abstract: AIM:To study adherence to the widely accepted surveillance guidelines for patients with long-standing colitis in the Netherlands. METHODS:A questionnaire was sent to all 244 gastroenterologists in the Netherlands. RESULTS:The response rate was 63%. Of all gastroenterologists, 95% performed endoscopic surveillance in ulcerative colitis (UC) patients and 65% in patients with Crohn's colitis. The American Gastroenterological Association (AGA) guidelines were followed by 27%, while 27% and 46% followed their local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(28 citation statements)
references
References 13 publications
3
23
2
Order By: Relevance
“…Our finding was consistent with prior studies of varied compliance with practice guidelines, in particular the low use of surveillance colonoscopy (25%) for patients with longstanding UC in an integrated healthcare delivery system in the USA [18,19,20,21,22]. IBD patients in our study sample presumably had CRC associated with longstanding colitis, although the retrospective nature of our study precluded detailed information on the duration, extent and severity of colitis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our finding was consistent with prior studies of varied compliance with practice guidelines, in particular the low use of surveillance colonoscopy (25%) for patients with longstanding UC in an integrated healthcare delivery system in the USA [18,19,20,21,22]. IBD patients in our study sample presumably had CRC associated with longstanding colitis, although the retrospective nature of our study precluded detailed information on the duration, extent and severity of colitis.…”
Section: Discussionsupporting
confidence: 82%
“…Adherence to surveillance colonoscopy guidelines for patients with ulcerative colitis (UC) has varied in clinical practice. Surveys of gastroenterologists showed that most gastroenterologists performed some form of surveillance for UC patients [18,19,20]. However, one survey suggested that only about half of IBD specialists and community gastroenterologists would recommend surveillance colonoscopy for a hypothetical patient with left-sided colitis [21].…”
Section: Introductionmentioning
confidence: 99%
“…This might be explained by the fact that only 12 % of our patients were included in a dysplasia surveillance programme before development of CRC, against a slightly higher percentage (15 %) in the academic cohort. Surveillance colonoscopies are not yet common practice in general hospitals in the Netherlands and most gastroenterologists in the Netherlands do not adhere to surveillance guidelines [25]. This low adherence to colonoscopy surveillance in IBD patients reflects clinical practice in general hospitals with a presumed perception of low CRC risks in these populations.…”
Section: Discussionmentioning
confidence: 99%
“…(90) Furthermore, the overall utilization of surveillance colonoscopy programs at the population level has been demonstrated to be low, with only a quarter of patients undergoing surveillance at recommended intervals. (91, 92) Even among high risk individuals (PSC), adherence to guidelines is reported to be less than 40%. (9194) Thus, irrespective of the interval or strategy followed, adherence to any surveillance program would be considered an optimization of current practices.…”
Section: Screening and Surveillancementioning
confidence: 99%
“…Providers have traditionally failed to comply with biopsy protocols, with some reports documenting adherence to be less than 5%. (92, 93, 95, 96) It is unclear if this variation in practice and adherence to surveillance techniques is due to patient preferences, provider practice preferences, or technical challenges (i.e. time required to submit multiple biopsies in multiple sample jars),(97) but it may help to explain why the rate of early/missed CRC after colonoscopy is reported to be nearly 15% among IBD patients as compared to only 5% in non-IBD patients.…”
Section: Screening and Surveillancementioning
confidence: 99%